Quantitative determination of selected heavy metals and micronutrients in branded dairy products sold in Nigeria using Atomic Absorption Spectroscopy (AAS) - Sunday Nwankwo Okafor; Chinenye Josse Okafor; Emmanuella Tochukwu Ogbonna; Chinelo Ezenwafor; Patience Ogoamaka Osadebe (African Journal of Pharmaceutical Research and Development (AJOPRED), 2024)
Quantitative analysis of heavy metals and nutrients in food helps indicate the safety and quality of food for final consumers. The present  study was conducted to assess the presence of heavy metals (arsenic, copper, mercury, chromium, and lead) and the nutritional value of  calcium in branded milk and yogurt to evaluate health risks for consumers. Ten (10) samples of branded milk and dairy products  manufactured in Nigeria were purchased. The metal contents of the samples were determined using atomic absorption spectroscopy.  The concentrations of calcium in the milk samples were between 9.33 ± 0.0023 and 18 ± 0.0071 ppm and were detected in all samples.  Arsenic concentrations ranged from 0.45 ± 0.00042 to 2.48 ± 0.00064 ppm in eight branded samples but were undetected in two samples.  Chromium levels were undetected in most samples, except for two with concentrations of 0.12±0.00049 ppm and 0.23±0.00021 ppm, respectively. Copper ranged from 0.032±0.00021 ppm to 0.129±0.00021 ppm in six samples. Mercury levels were detected in six samples  at a concentration of 1.0±1.0 ppm. Lead concentrations ranged from 0.15±0.00064 to 0.29±0.00028 ppm in three samples. The study found heavy metals above the ideal concentration in branded milk and dairy products in Nigeria, highlighting the need for quality control  measures during production to prevent contamination.